Case report: Esophageal bulge with white patch: endoscopic removal of leiomyoma and high-grade intraepithelial neoplasia - Pan, Lili; Zhang, Chong; Ma, Ran; Fan, Lijuan (Frontiers in Oncology, 2024)
Esophageal leiomyoma is the most common benign intramural tumor of the esophagus. Despite being the most common benign tumor in its category, esophageal leiomyomas constitute only 1.2% of all esophageal tumors. While esophageal leiomyoma itself is uncommon, the occurrence of multiple esophageal leiomyomas is even rarer, and the coexistence of high-grade squamous intraepithelial neoplasia (HGIN), involving both epithelial and mesenchymal tissues, is exceedingly rare. This case report describes a patient with multiple esophageal leiomyomas and localized HGIN, diagnosed using endoscopic ultrasonography, which identified a submucosal lesion within the muscularis mucosae. The lesion was successfully treated using endoscopic high-frequency electrocoagulation resection. This minimally invasive approach proved to be precise, safe, and effective, offering therapeutic outcomes comparable to those of traditional surgical resection, as confirmed by postoperative pathological analysis. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract. Leave the Abstract empty if your article does not require one – please see the “Article types” on every Frontiers journal page for full details.